The Impact of Parental Self-Efficacy in Self-Care on the Independence of Children with Autism Spectrum Disorder - Septian Andriyani; Sehabudin Salasa; Suci Tuty Putri; Farida Murtiani; Dadang Darmawan (GLOBAL HEALTH SCIENCE GROUP, 2026)
ASD is characterized by challenges in social communication, restricted interests, and repetitive behaviors, significantly impacting daily functioning and self-care abilities in affected children. The prevalence of ASD has been rising, making effective treatment and rehabilitation essential. The study explores the influence of parental self-efficacy on the independence of children with Autism Spectrum Disorder (ASD). The research utilized a quantitative correlational analysis with a cross-sectional design involving 53 parents of children diagnosed with ASD. Total sampling was employed to gather data, focusing on how parental self-efficacy, defined as the confidence parents have in their ability to manage parenting tasks, affects their children's independence. The research location was Our Dream Indonesia in Bandung, West Java, Indonesia. To measure parental self-efficacy, the Self-Efficacy for Parenting Tasks Index (SEPTI) by Coleman and Karraker (2000) was used, adapted into Indonesian. To measure child independence, the Waisman Activity of Daily Living Scale (W-ADL) was modified and adapted to the child's developmental stage. The validity test results for the Self-Efficacy value are in the range of 0.347-0.771, and a Cronbach's alpha reliability value of 0.718-0.834. Cronbach's alpha reliability results range from 0.88 to 0.94, and a validity value of 0.78-0.82. The results of the reliability test showed that the Cronbach's Alpha value was 0.875, and the independence questionnaire was 0.791. The data analysis process used univariate and bivariate analysis. Univariate analysis was conducted to determine frequency distribution and central tendency, and bivariate analysis was used linear regression to examine the closeness of the relationship between variables. The findings indicated that self-efficacy accounted for 29% of the variance in children's independence as measured by the coefficient of determination (R² = 0.29). This suggests that higher levels of parental self-efficacy are associated with increased independence in children with ASD. The study concludes that enhancing parental self-efficacy is crucial for improving children's ability to meet their daily needs independently. This aligns with existing literature that emphasizes the role of parental confidence in managing the complexities of raising a child with autism. Parents who feel more competent are likely to engage more effectively in their child's care and therapy, ultimately fostering better outcomes for their children.